Clinical study of anemia in women attending the College of Medical Sciences Bharatpur - Pradhan, M (Journal of College of Medical Sciences-Nepal, 2015)
OBJECTIVE To study the clinical profile of Anemia in Women attending the College of Medical Sciences-Teaching Hospital, Bharatpur, Chitwan. MATERIALS & METHODS The Study was conducted among 100 women patients attended to the College of Medical Sciences- Teaching Hospital, Bharatpur, Chitwan. Their blood samples were tested and related socio-demographic information was collected. The associated Clinical signs and symptoms with hemoglobin level and the occurrence of anemia were assessed. RESULT The peak incidence of Anemia was in the age group of 20-24 yrs (59.7%), and severity of anemia was correlated with sings and symptoms. Majority of them had Microcytic Hypochromic anemia (43.1%) with serum iron level below normal level and increased TIBC (total iron binding capacity) were observed. CONCLUSION The high prevalence of Nutritional anemia suggests the dietary advice to be emphasized strongly. Journal of College of Medical Sciences-Nepal, 2014, Vol-10, No-3, 23-28